PENGARUH PELAYANAN PINJAMAN KREDIT TERHADAP KEPUTUSAN MEMBELI PADA PT. BESS FINANCE CABANG LEUWILIANG BOGOR - Prasetya, Syarief Gerald (STIE Binaniaga, 2013)
Quality of care is the central point for service companies because it will mempengruhi customer satisfaction. It is intended that all the goods or services being offered will have a good place in the eyes of society. Customer satisfaction will occur if service quality is good, where good service quality includes five dimensions of service quality, namely: physical evidence (tangible), reliability (realibility), responsiveness (responsiveness), assurance (assurance), several benefits, including relationships between the company and its customers to be harmonious, allowing repurchase and creation of customer loyalty and member recommendation by word of mouth (word of mouth) that benefit the company. Provide the best services, responsiveness dimension includes the willingness of employees to help customers and provide prompt delivery, assurance dimension includes courtesy of employees and their ability to evoke a sense of trust and confidence of consumers, as well as the dimensions of empathy that includes a sense of caring and concern given to the customer. The fifth dimension beyond so-called SERVQUAL (service quality), which is an instrument measuring the quality of service.Keyword:Service quality